Winter rye cultivars moderately resistant to ergot - L. M. Shchekleina; T. K. Sheshegova (Труды по прикладной ботанике, генетике и селекции)
Background. Cereal ergot caused by the fungus Claviceps purpurea (Fr.) Tul. is a progressive disease of winter rye. There are no rye cultivars resistant to the disease, and breeding methods of protection have not been developed in Russia.Materials and methods. The material for the research included 97 winter rye cultivars. A biochemical analysis of the sclerotia of the fungus was carried out, the composition and content of ergot alkaloids (EA) in the sclerotia of C. purpurea from the Kirov population were studied, and the relationship between the biometry of sclerotia and the EA content, toxicity and pathogenicity of C. purpurea was analyzed. Well-known methods of resistance assessment and EA analysis were applied.Results and conclusions. Fourteen cultivars least affected by the pathogen were identified: ‘Flora’, ‘Kiprez’, ‘Grafinya’, ‘Lika’, ‘Batist’, ‘Simfoniya’, ‘Garmoniya’, ‘Sadko’, ‘Parom’, ‘Virazh’, ‘Saratovskaya 7’, ‘Volkhova’, ‘Novaya Era’, and ‘Podarok’. They can be used in breeding for ergot resistance. Three types of EA were identified in C. purpurea sclerotia: ergocristine, ergotamine, and its stereoisomer ergocristinine. Cvs. ‘Lika’, ‘Simfoniya’ and ‘Garmoniya’ were the least affected by ergot, and the sclerotia formed on the plants of these cultivars did not accumulate EA. A significant (r = 0.50–0.60) correlation was found between lesions and biometric parameters of C. purpurea sclerotia, and between grain contamination with sclerotia and their biometrics (r = 0.63– 0.78). A weak positive correlation (r = 0.22) was detected between the toxicity and pathogenicity of C. purpurea. A negative correlation was established between the weight of sclerotia and the accumulation of EA in them (r = –0.46), which indicated the biological danger of small sclerotia that got into the seed and food batches of grain.